Adipokines, Cardiovascular Risk, and Therapeutic Management in Obesity and Psoriatic Arthritis - Porta, Sabrina; Otero-Losada, Matilde; Kölliker Frers, Rodolfo A.; Cosentino, Vanesa; Kerzberg, Eduardo; Capani, Francisco (Frontiers in Immunology, 2021)
Psoriatic arthritis is a chronic inflammatory disease with skin and joint pathology as the dominant characteristics. Scientific evidence supports its systemic nature and relevant relationship with obesity, metabolic syndrome, and associated conditions. Metabolic syndrome and obesity share common signaling pathways with joint inflammation, reinforcing the idea that adipose tissue is a major contributor to disease development and severity. The adipose tissue is not a mere energy store but also an endocrine organ participating in the immune response. In the search for the best therapeutic strategy for a patient, we should appraise the adipose tissue as an endocrine and immune organ responsible for mild chronic inflammation. Today, our challenge is not only to achieve disease remission but to control the associated comorbidities as well. In light of the high prevalence of obesity in psoriatic arthritis patients and the importance of the adipose tissue in the development of chronic inflammation, we aimed to identify the most relevant articles in this regard published in English until June 2020 using the PubMed database. Search terms included psoriatic arthritis, in combination with metabolic syndrome, obesity, adipokines, cardiovascular disease, and treatment. This review summarizes the current evidence regarding the role of adipose tissue as an adipokine-secreting endocrine organ, discussing its influence on disease development and severity, and ultimately in meeting successful disease management.